Hydrogenation of plasma-excited nitrogen over an alumina catalyst for ammonia synthesis. (9th August 2018) - Xie, Qinglong; Zhuge, Shaoyuan; Song, Xiaofang; Lu, Meizhen; Ruan, Roger; Nie, Yong; Ji, Jianbing
Abstract: Ammonia (NH3 ) is a potential hydrogen carrier as alternative fuel and feedstock for hydrogen production. In this study, plasma synthesis of NH3 was conducted in a packed-bed dielectric barrier discharge (DBD) reactor using Al2 O3 as the catalyst. In order to explore the mechanism of hydrogenation of plasma-excited nitrogen for NH3 synthesis, the whole NH3 synthesis process was divided into three steps including N2 activation, hydrogenation of plasma-excited N(a), and desorption of NH3 (a) from catalyst. The effects of reaction conditions on the three steps and corresponding NH3 production were examined. Results showed that more plasma-excited nitrogen species were formed through N2 activation at higher N2 flow rate, discharge time and discharge power for N2 activation. Hydrogenation of plasma-excited N(a) to form NH3 (a) was improved by more discharge time at the second step. Higher discharge temperature for N(a) hydrogenation favored NH3 (a) desorption from catalyst and increased NH3 production at the second step, with the total NH3 yield slightly changed. In addition, one-step NH3 synthesis in plasma was investigated and compared with the three-step process. The results will provide reference for catalyst and reactor design in plasma synthesis of ammonia. Highlights: A novel method of studying the mechanism of plasma synthesis of NH3 is provided. The whole NH3 synthesis process is divided into three successive steps. More discharge time and higher discharge power favor N2 activation at the first step. Hydrogenation of N(a) is improved by more discharge time at the second step. NH3 (a) desorption at the third step is greatly influenced by discharge temperature.